2023
DOI: 10.1136/bmjopen-2022-064174
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of post-dialysis fatigue: a systematic review and meta-analysis

Abstract: ObjectivesThe purpose of this study was to synthesise data on the prevalence of post-dialysis fatigue (PDF) among haemodialysis (HD) patients.DesignSystematic review and meta-analysis.Data sourcesChina National Knowledge Infrastructure, Wanfang, Chinese Biological Medical Database, PubMed, EMBASE and Web of Science were searched from their inception to 1 April 2022.Eligibility criteriaWe selected patients who must receive HD treatment for at least 3 months. Cross-sectional or cohort studies published in Chines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…1 Most patients are treated with in-center hemodialysis, a time-intensive modality requiring thrice-weekly, in-person treatments at dialysis centers followed by prolonged postdialysis symptoms. 2 Research has suggested that some patients and clinicians prefer dialyzing at home, 3 , 4 , 5 which allows for greater flexibility and independence, shorter recovery times, and some improved mortality outcomes. 6 , 7 As of 2021, about 14.1% of prevalent patients received home dialysis, 1 with higher use among White patients compared to Black or Hispanic patients, even though as many as 85% of patients are thought to be medically eligible for this service.…”
Section: Introductionmentioning
confidence: 99%
“…1 Most patients are treated with in-center hemodialysis, a time-intensive modality requiring thrice-weekly, in-person treatments at dialysis centers followed by prolonged postdialysis symptoms. 2 Research has suggested that some patients and clinicians prefer dialyzing at home, 3 , 4 , 5 which allows for greater flexibility and independence, shorter recovery times, and some improved mortality outcomes. 6 , 7 As of 2021, about 14.1% of prevalent patients received home dialysis, 1 with higher use among White patients compared to Black or Hispanic patients, even though as many as 85% of patients are thought to be medically eligible for this service.…”
Section: Introductionmentioning
confidence: 99%